2021
DOI: 10.33448/rsd-v10i8.17494
|View full text |Cite
|
Sign up to set email alerts
|

Forage productivity and chemical composition of Panicum maximum cv. Mombaça under defoliations intensities and frequencies

Abstract: The effects of defoliation frequency (28, 35, 42 and 49 days) and defoliation intensity (30, 40 and 50 cm above the ground) on green dry matter (GDM) yield, and chemical composition of Panicum maximum cv. Mombaça were evaluated under natural field conditions at the Roraima´s savannas. Defoliation regimes affect productivity and chemical composition of grass forage. The decrease in the pasture defoliation frequency and intensity improved the accumulation of forage, however it reduces the tissue concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Considering an available use efficiency forage of 50% and an average daily intake of 11.25 kg of GDM AU -1 (AU = 450 kg of live weight), which represents 2.5% of the animal's live weight (Costa, 2014;Costa et al, 2021). So the availability of GDM record in this work would provide grazing periods of 20.2; 32.1; 38.1 and 46.2 days, respectively for rest periods of 14, 28, 42 and 56 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering an available use efficiency forage of 50% and an average daily intake of 11.25 kg of GDM AU -1 (AU = 450 kg of live weight), which represents 2.5% of the animal's live weight (Costa, 2014;Costa et al, 2021). So the availability of GDM record in this work would provide grazing periods of 20.2; 32.1; 38.1 and 46.2 days, respectively for rest periods of 14, 28, 42 and 56 days.…”
Section: Resultsmentioning
confidence: 99%
“…Cruz et al (2021) reported an inverse relationship between appearance and expansion of leaves, as the greater the speed of appearance of leaves, the shorter the period available for their expansion. The LER has a high correlation with GDM grass production and has been use as a criterion for grass selection in genetic improvement works, as it is directly relate to the final leaf length, as smaller leaves are usually associated with higher LAR values (Nabinger & Carvalho, 2009;Pereira, 2013;Martuscello et al, 2019;Costa et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency and intensity of defoliation influence the production of dry and green matter and the chemical composition of Panicum maximum cv. Mombasa and proper management can provide greater forage productivity and quality, regrowth vigor, greater forage utilization efficiency, remarkable tissue renewal, and a more favorable canopy structure for grazing [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the same author De Sousa et al (2019) informed similar plant height values than to the obtained by us in tropical Ecuadorian conditions at grazing frequencies of GF30 (55 vs. 49 cm) or GF60 (70 vs. 86 cm). Whereas the reduction in defoliation intensity allows the retention of greater leaf area photosynthetically active and greater remobilization of nutrients, resulting in greater speed of recovery and shorter interval between grazing (Costa et al, 2021). In this sense, Euclides et al (2018) mentioned that, despite high DM/ha -1 obtained on forages managed at 30 cm, these forages need more days to reach suitable target height, resulting in fewer grazing cycles compared to forages at > 50 cm of CHs.…”
Section: Agronomic Measurementsmentioning
confidence: 99%
“…As a result, for our conditions, the best combination regarding DM/ha -1 , the Tanzania grass should be managed at GF30 and 45 cm of CHs, to restore their organic reserves, especially non-structural carbohydrates and the formation of new leaves, which would favour the appearance of a new generation of tillers (Costa et al, 2021). In summary, an adequate management of pastures, defoliation intensity and frequency need to be reconciled, in order to ensure forage productivity and quality, and mainly its persistence.…”
Section: Agronomic Measurementsmentioning
confidence: 99%